Palm-Based Biodiesel Blend Mandate Increase on the Biodiesel Industry Growth in Malaysia: Evidence from Causal Loop Diagram - Zabid, M. Faeid M.; Zainal Abidin, Norhaslinda; Applanaidu, Shri Dewi (2016)
The government recent announcement to increase blend mandate of BIO for transportation sector and 87 for industrial sector has being deemed by expert as a huge turning point to Malaysia palm based biodiesel industry growth. However, this has attract several concerns on the viability of the industry especially during the low crude oil price period. To analyse this issue, the causal loop diagram of system dynamics method was built to explain the conceptual idea of developed model. The result found positive value from environmental and wide economic perspective despite negative value from cost-profit perspective. This study is important in changing current unfavourable perception towards government commitment in promoting the growth of biodiesel industry in Malaysia. Future works include thorough technical analysis using full stock and flow diagram as a continuum from this study.